Diurval Variation Of PM10 And Carbon Monoxide Concentrations In Penang - Abd. Manaff, Liana Syafinaz (Universiti Sains Malaysia, 2005)
Pollution is not a very important matter long time ago since it does not give any big impact to human life. But it becomes to be a big issue now since there are a lot of pollution occurred in many places. Though some pollution comes from these natural sources, but most pollution is the result of human activity. The main sources are vehicle and industrial emissions. Air quality is deteriorating in most cities in the world due to a huge addition in the number of motor vehicles on the road. Therefore, this study is done to discuss about the main sources which contribute to the increasing air pollution in Prai. Furthermore, the impacts and mitigation steps that should be taken are also discussed in order to upgrade the air quality in Prai. This report will give a good overview about air pollution in Prai, Penang.